Rheological assessment of the interaction between hydrophobic nanoclay and xanthan gum in saline environment, for application in drilling nanofluid (Research, Society and Development, 2020)
In the last decade, exploration in high temperature and pressure wells has motivated the improvement of drilling fluids with the application of nanoparticles. In this context, nanoclay, the most available of nanoparticles, has been applied in the development of nanofluids, mainly associated with polymers. In parallel, among the polymers used, xanthan gum has been little explored for this purpose. In this work, the interaction between xanthan gum, hydrophobic nanoclay, sodium and calcium chloride and their influence on the rheological parameters of the mixture was evaluated in solution. The influence of temperature and hydration time on the rheological parameters of the mixture was also evaluated. For this purpose, nanoclay was first characterized with XRF, XRD and TGA. Then, a complete factorial design 24 was adopted, varying the concentrations of nanoclay, xanthan, sodium and calcium chlorides. Third, a Doehlert Matrix of the 7x5x3 type was adopted, varying the concentrations of nanoclay, xanthan and temperature, with the concentrations of the constant salts. In the fourth, select the effect of the hydration time on the color rheological parameters. Finally, Conductivity and Potential Zetas of sizes were verified, varying the concentration of the components and the hydration time of the mixtures. It was concluded that the interactions between the components of the mixture do not stabilize; the temperature, the salts have no significant influence on the rheology of the mixture; nanoclay in concentrations not exceeding 5% (m/v) interacts with the Minimum Shear Stress; the rheological parameters stabilize after 96h of hydration.